Pengaruh Sambungan Beton Pracetak Hollow Block terhadap Pola Retak yang Timbul - Bunyamin Bunyamin (Jurnal Serambi Engineering, 2020)
Hollow block precast concrete which was combined into a beam casting by adding concrete and steel inside and called as “hollow block reinforcement concrete beam”. The aim of this research was to knowing the crack pattern due to the connection of hollow block reinforcement concrete beam. The specification of ACI (American Concrete Institute) 211.3R-02 and ASTM (American Society for Testing of Materials) were used in this research. The object were two normal reinforcement concrete beam and two hollow block reinforcement concrete beam with size 15 cm x 20 cm x 210 cm. The reinforcement concrete beam was tested by using load cell. The result showed the variety of crack pattern which are flexural crack and flexural-shear crack. For normal reinforcement concrete beam, flexural crack formed at 0.95 ton and flexural-shear crack at 2.83 ton with its duration was 5 minutes and 29 seconds. For hollow block reinforcement concrete beam, flexural crack formed at 1.16 ton and flexural-shear crack at 1.98 ton with its durat on was 6 minutes and 8 seconds. The result also showed that hollow block reinforcement concrete beam was more ductile due to crack pattern than normal reinforcement concrete beam.